Influence of parental smoking on smoking habit of Bangladeshi adult population in rural and urban areas - Meerjady, Sabrina Flora; CGN, Mascie-Taylor; Rahman, Mahmudur; Akter, Seikh Farid Uddin (Centre for Promoting Ideas (CPI), USA, 2012)
Aim: To examine whether smoking status of adult Bangladeshis was influenced by their parental smoking behaviour. Study design: Descriptive cross sectional study. Place and duration of study: A community-based study was conducted in urban and rural areas of Bangladesh during the period from 2001 to 2003. Methodology: Data of the cross-sectional study involving 35,446 (16,196 males and 19, 250 females) adults in urban and rural Bangladesh were analyzed in 2007. Data were collected on their smoking pattern and parents’ smoking habit by interview. Results: Among the total study subjects, 67.8% and 15.2% reported that their fathers and mothers smoked, respectively, and 14% reported that both parents smoked. In both sexes, current smokers and ever smokers were more often found among respondents when both parents smoked. Smoking was also higher than expected if one parent smoked; this was especially true, for father and son and mother and daughter combinations. The mean (SD) reported age of commencing smoking was 17.8 (5.0) years. Both males and females started smoking at an earlier age if both their parents smoked, compared with only one parent smoking. Conclusion: Parental smoking influences smoking habit and age of starting to smoke of their offspring. Future prevention programs might need to give special attention to the individuals having smoking parents.